Fatty liver index as a predictor of increased risk of cardiometabolic disease: finding from the Kuopio Ischaemic Heart Disease Risk Factor Study Cohort - Tomi-Pekka Tuomainen; Jussi Pihlajamäki; Olubunmi O. Olubamwo; Jyrki K. Virtanen; Pekka Mantyselka (BMJ Open)
Objective Fatty liver disease (FLD), a global epidemic, is also a predictor of cardiometabolic disease (CMD) (type 2 diabetes or cardiovascular disease). Our objective was to examine whether progressive FLD, as assessed by fatty liver index (FLI), predicts increasing future CMD risk compared with relatively stable FLD, among middle-aged men.Design Prospective epidemiological study.Setting University affiliated research centre in Kuopio, Eastern Finland.Participants Our subjects were 501 men without CMD during the initial 4-year follow-up in the Kuopio Ischaemic Heart Disease Risk Factor Study cohort.Outcome measure Over the initial 4-year follow-up, 135 men (26.9%) had a significant (≥10) FLI increase. The association of 4-year FLI increase with incident CMD was analysed in multivariable-adjusted Cox regression models, adjusting for baseline constitutional and lifestyle factors (model 1) and, in addition, metabolic and inflammation biomarker factors (model 2).Results During a mean follow-up of 15 years, 301 new CMD cases occurred. We used subjects with low baseline FLI and no significant 4-year FLI increase as the reference. For subjects with intermediate baseline FLI and significant 4-year FLI increase, the HRs and 95% CIs for incident CMD in model 1 (2.13 (1.45 to 3.13)) and model 2 (1.73 (1.13 to 2.66)) exceeded values for subjects with similar baseline FLI without a significant 4-year change (HRs (95% CIs) were 1.36 (0.94 to 1.97) for model 1 and 1.18 (0.81 to 1.70) for model 2). They approached HRs (95% CI) for subjects who maintained high FLI over the 4 years (HRs (95% CIs) were 2.18 (1.54 to 3.10) in model 1 and 1.85 (1.21 to 2.82) in model 2).Conclusion Persons with significant FLI increase are likely with increasing CMD risk. Such persons should be evaluated for progressive FLD and CMD and managed to reduce CMD risk.